Digital soil mapping with limited data - Hartemink, Alfred E.; McBratney, Alex; Mendonca-Santos, María de Lourdes
here has been considerable expansion in the use of digital soil mapping technologies and development of methodologies that improve digital soil mapping at all scales and levels of resolution. These developments have occurred in all parts of the world in the past few years and also in countries where it was previously absent. There is almost always a shortage of data in soil research and its applications and this may lead to unsupported statements, poor statistics, misrepresentations and ultimately bad resource management. In digital soil mapping, maximum use is made of sparse data and this book contains useful examples of how this can be done. This book focuses on digital soil mapping methodologies and applications for areas where data are limited, and has the following sections (i) introductory papers, (ii) dealing with limited spatial data infrastructures, (iii) methodology development, and (iv) examples of digital soil mapping in various parts of the globe (including USA, Brazil, UK, France, Czech Republic, Honduras, Kenya, Australia). The final chapter summarises priorities for digital soil mapping